Preparation and characterisation of calcined Mg/Al hydrotalcites impregnated with alkaline nitrate and their activities in the combustion of particulate matter - Comelli, Nora Alejandra (2013)
The effect of incorporating alkaline nitrates in hydrotalcites for use in the combustion of particulate matter from diesel emissions has been studied. The catalysts were characterised by X-ray diffraction (XRD), N2 adsorption, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), elemental analysis (EA), atomic absorption spectrophotometry (AAS) temperature programmed reduction (TPR) and Fourier transform infrared spectroscopy (FTIR). Activity measurements were carried out using a thermobalance in air and using a fixed-bed reactor with a NO/O2 flow. The observed activities decreased in the following order: HTMgAlcCs > HTMgAlcK > HTMgAlcLi > HTMgAlc.